COMPETITIVENESS OF DESTINATIONS WITHIN THE RURAL TOURISM CLUSTER: ZLATAR, ZLATIBOR - Pavlović, Sanja; Čavlin, Gordana (Economics of Agriculture, 2014)
Cluster analysis is gaining increasing importance in the contemporary development of tourism. These are mostly areas that have similar tourist values. This paper presents the competitiveness of tourist destinations in the cluster of rural tourism Zlatar, Zlatibor, as defned in the Master Plan for Sustainable Development of Rural Tourism in Serbia. Having used AHP (Analytic Hierarchy Process) criteria pairs have been frst compared, and then the alternatives (villages of Zlatar and Zlatibor). The seven criteria used in this paper are the following: factors and attractors, accessibility and infrastructure, accommodation facilities, unemployment, experience in rural tourism, proximity of the marketplace, and seasonality. The AHP method has been used to determine relations between the influence factors and the dominance of one factor in relation to another.It has been noted a relatively weak dominance of the villages of Zlatibor, by all criteria, except when it comes to unemployment, which is dominated by the villages of Zlatar.